JUSTIÇA DE TRANSIÇÃO NO BRASIL: a questão da responsabilização penal por graves violações a direitos humanos - Barreto, Renata Caldas (2015)
The work talks about the responsabilization of public officials for serious violations of human rights perpetrated during the brazilian dictatorship, which have occurred between the years 1964-1985. This way of confronting the authoritarian legacy includes the Transitional Justice Knowledge course and, close to the respect for the right to the truth and the memory, repair and reform of the institutions, contribuited to the consolidation of a democratic state of the law. Despite the importance of these activities, Brazil, by the year 2015, did not realized any condemnation for abuses of the authoritarian past. From the analysis of criminal actions pending in federal court by the year 2015, it was identified that the amnesty conveyed in Law 6,683/79 (Amnesty Law) constitutes a major legal obstacle to the effectiveness of criminal prosecution of state agents. It points up, as a way to overcome the obstacle of the amnesty, the use of the argument of the existence of crimes against humanity, and the need for agencies of the Brazilian justice system realize the conventionality control of normative acts.